1992
DOI: 10.1007/bf01321721
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a peer health worker prenatal outreach and education program for Hispanic farmworker families

Abstract: This article contains the findings from an evaluation of a prenatal education program to Hispanic migrant farmworker families using peer health workers. The focus of the evaluation was on establishing the validity of the intervention model in the target population. Data are presented on the program setting, characteristics of the clients served, and effects of the educational program on the clients and peer health workers. The evaluation identified factors that established confidence in the program model: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…This supports research showing that the mothers' self-determination, decision-making, and self-efficacy increased after participating in CHW programs~Holden, 1999;Larson et al, 1992;Watkins et al, 1990;Warrick et al, 1992!. Although significant change over time was seen and indicates a significant impact of the MOMobile program on the mothers, we cannot directly state that the relationship with the advocate caused this change to occur.…”
Section: Changes In Empowermentsupporting
confidence: 84%
See 1 more Smart Citation
“…This supports research showing that the mothers' self-determination, decision-making, and self-efficacy increased after participating in CHW programs~Holden, 1999;Larson et al, 1992;Watkins et al, 1990;Warrick et al, 1992!. Although significant change over time was seen and indicates a significant impact of the MOMobile program on the mothers, we cannot directly state that the relationship with the advocate caused this change to occur.…”
Section: Changes In Empowermentsupporting
confidence: 84%
“…concluded that after working with a CHW program during pregnancy and throughout the following year, low-income parents reported an improved selfassessment of parenting skills and abilities. Research has demonstrated that parenting and psychoeducational support programs improve parenting skills and may reduce the rates of subsequent child abuse and neglect~Budd, Heilman, & Kane, 2000;DePaul & Domenech, 2000;Dukewich, Borkowski, & Whitman, 1996;McCullough & Scherman, 1998;Prater, 1995;Schamess, 1990;Zuravin & DiBlasio, 1992!. Many of the psychosocial risk factors associated with both teen parenthood and child maltreatment may be significantly altered with the support that psychoeducational Meister, & de Zapien, 1992! noted that a peer worker prenatal outreach program fostered social cohesion, leading to increased interactions between clients and healthcare workers.…”
Section: Community Health Workers~chws! Have Played An Important Rolementioning
confidence: 95%
“…The relationship between the living environment and child health outcome has been widely acknowledged [13,[38][39]. The disadvantages of living in a poor environment on gaining maternal health literacy need attention while health education programs are provided.…”
Section: Discussionmentioning
confidence: 99%
“…These initiatives address several aspects for improving the delivery of health services, including conducting culturally appropriate community health assessments (14,15), using clinic models (79,108), using culture brokers and outreach workers to improve service delivery (52,98), and using lay health advisors (35,102,103). There are no evaluations of these programs or indicators of whether the programs have continued or if they have been replicated in other locales.…”
Section: Farmworker Health Services Programsmentioning
confidence: 99%